Role of insulin resistance in essential hypertensive patients in Qena Governorate, Egypt - Mohamed Alsenbsey; Basem Asham; Sanaa Shaker Aly; Samar Sayed Ahmed; Ahmed Boghdady (Wolters Kluwer Medknow Publications, 2018)
Introduction Essential hypertension is associated with multiple metabolic abnormalities; one of the most important is hyperinsulinemia. On the contrary, euglycemic state has been elicited in hypertensive patients. Aim To explore the pathogenic role of hyperinsulinemia in essential hypertensive patients even with euglycemia. Patients and methods A total of 60 euglycemic patients (30 hypertensive patients and 30 normotensive controls) were recruited in a case-control study. Blood pressure, insulin level, lipid profiles, BMI, and waist circumference (WC) were estimated for both groups. In addition, the severity of hypertension was classified according to the European hypertension guidelines. Results Significant increases of fasting insulin level, BMI, WC, and dyslipidemia (increase total cholesterol, triglycerides, and low-density lipoprotein-cholesterol) and a significant decrease of high-density lipoprotein-cholesterol in hypertensive patients than the controls were found. Moreover, a highly significant correlation was detected between the severity of hypertension and the parameters of fasting insulin level, BMI, WC, and triglycerides level. Conclusion The study showed a significant increase in fasting insulin level in hypertensive patients than the control group. Besides, there was a highly significant increase of fasting insulin level with hypertension severity; therefore, this supports a possible pathogenic role of hyperinsulinemia (through insulin resistance) in the onset of hypertension even when the fasting blood sugar is within the normal limits (euglycemic).